2012
DOI: 10.1111/j.1365-2591.2012.02053.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth discoloration induced by endodontic materials: a laboratory study

Abstract: Materials used in endodontics may stain teeth. Therefore, the choice of material should not rely solely on biological and functional criteria, but also take aesthetic considerations into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
271
3
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(300 citation statements)
references
References 30 publications
(45 reference statements)
13
271
3
13
Order By: Relevance
“…Previous laboratory and clinical studies have reported dental discoloration after using MTA. 17,19,21 Therefore, it is necessary to study if the agent responsible for the color alteration without the interference of other factors such as blood, dentin or saliva is actually the cement or its metallic components (bismuth). The ∆E observed for all the tested materials was higher than 3.3, which is not considered clinically acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous laboratory and clinical studies have reported dental discoloration after using MTA. 17,19,21 Therefore, it is necessary to study if the agent responsible for the color alteration without the interference of other factors such as blood, dentin or saliva is actually the cement or its metallic components (bismuth). The ∆E observed for all the tested materials was higher than 3.3, which is not considered clinically acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Color alteration of calcium silicate-based cements has been reported. 17,[19][20][21] It has been suggested that the radiopacifier bismuth oxide, present in the MTA composition, is the main cause of dental discoloration. 22 Furthermore, it has been previously demonstrated that AH 26 sealer, which also contains bismuth oxide, results in tooth discoloration.…”
Section: Introductionmentioning
confidence: 99%
“…A descoloração dentária é uma consequência indesejável de algumas reações químicas verificadas para determinados materiais quando em contato com as estruturas dentárias (JACOBOVITZ; DE PONTES LIMA, 2009;BELOBROV;PARASHOS, 2011;LENHERR, et al, 2012). Em tratamentos que envolvem áreas com comprometimento estético, a estabilidade de cor dos cimentos é fundamental.…”
Section: Cimento Portland Com 50% De Tungstato De Cálciounclassified
“…Tais íons encontram-se na forma de silicato tricálcio, silicato dicálcio, aluminato tricálcio e aluminoferrita tetracálcio (CAMILLERI, 2008a LENHERR, et al, 2012;VALLES, et al, 2013aVALLES, et al, ,2013b. Esta característica é altamente indesejável para materiais endodônticos, principalmente quando utilizados em áreas com comprometimento estético como, por exemplo, em dentes anteriores.…”
unclassified
See 1 more Smart Citation